Psoriasis and Diabetes: A Multicenter Study in 222078 Type 2 Diabetes Patients Reveals High Levels of Depression. (17th August 2015) - Schwandt, Anke; Bergis, Dominik; Dapp, Albrecht; Ebner, Stefan; Jehle, Peter M.; Köppen, Stefan; Risse, Alexander; Zimny, Stefan; Holl, Reinhard W.
Abstract : Objective . This study aimed to investigate the association between psoriasis and disease outcome in type 2 diabetes (T2D). Methods . 222078 T2D patients (≥10 years old) from the prospective, multicenter diabetes patient registry were analyzed. Specific search items were used to identify psoriasis patients. Multiple regression models were fitted and adjusted for demographic confounder. Results . 232 T2D patients had comorbid psoriasis. After adjusting psoriasis patients revealed a higher BMI (31.8 [31.0; 32.6] versus 30.6 [30.5; 30.6] kg/m 2, p = 0.004 ) and HbA1c (64.8 [62.1; 67.6] versus 59.0 [58.9; 59.1] mmol/mol, p < 0.0001 ). Insulin was used more frequently (62.3 [55.7; 68.5] versus 50.9 [50.7; 51.1] %, p = 0.001 ), only OAD/GLP-1 was similar, and nonpharmacological treatment was less common (13.3 [9.5; 18.3] versus 21.9 [21.7; 22.1] %, p = 0.002 ). Severe hypoglycemia (0.31 [0.238; 0.399] versus 0.06 [0.057; 0.060] events per patient-year, p < 0.0001 ), hypertension (86.1 [81.1; 90.0] versus 68.0 [67.8; 68.2] %, p < 0.0001 ), and thyroid disease (14.0 [10.1; 19.2] versus 4.6 [4.5; 4.7] %, p < 0.0001 ) were more prevalent. Depression occurred more often (10.5 [7.1; 15.2] versus 2.8 [2.7; 2.8] %, p < 0.0001 ). Conclusions . Clinical diabetes characteristics in psoriasis T2D patients were clearly worse compared to patients without psoriasis. Comorbid conditions and depression were more prevalent, and more intensive diabetes therapy was required.